The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1148/rg.293085056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Interventional Radiology for Budd-Chiari Syndrome

Abstract: Budd-Chiari syndrome is a heterogeneous group of disorders characterized by hepatic venous outflow obstruction that involves one or more draining hepatic veins. Its occurrence in populations in the western hemisphere is commonly associated with hypercoagulative states. Clinical manifestations in many cases are nonspecific, and imaging may be critical for early diagnosis of venous obstruction and accurate assessment of the extent of disease. If Budd-Chiari syndrome is not treated promptly and appropriately, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 71 publications
0
73
0
7
Order By: Relevance
“…Patients with Budd-Chiari syndrome may be asymptomatic and discovered incidentally or present with symptoms on a spectrum ranging from mild abdominal pain to fulminant liver failure. The severity of disease on presentation is dictated by the degree and rate of onset of obstruction, as well as the development of compensatory collateral outflow (2). Following diagnosis, the goal of treatment is to decompress hepatic venous outflow in a timely manner to minimize damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with Budd-Chiari syndrome may be asymptomatic and discovered incidentally or present with symptoms on a spectrum ranging from mild abdominal pain to fulminant liver failure. The severity of disease on presentation is dictated by the degree and rate of onset of obstruction, as well as the development of compensatory collateral outflow (2). Following diagnosis, the goal of treatment is to decompress hepatic venous outflow in a timely manner to minimize damage to hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These therapies may alleviate symptoms temporarily but are not definitive treatments, and relying solely on medical management is associated with poor longterm outcomes. The well accepted definitive treatments of Budd-Chiari syndrome are endovascular (hepatic vein recanalization, TIPS) and surgical (shunt creation, liver transplant) procedures (2). Endovascular methods of decompression are preferred over surgical shunt creation as they are associated with lower morbidity and mortality, and liver transplantation is limited by donor availability and is reserved for patients with irreversible liver damage and advanced hepatocellular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Primer veya sekonder nedenlerle gelişen sendromda sinüzoidal basınç artmakta ve PV akımı azalmaktadır. Sentrlobüler konjesyona bağlı olarak nekroz ve atrofi gelişir [1,[4][5][6].…”
Section: Venöz Obstrüksi̇yon (Budd-chiari Sendromu)unclassified
“…Bu nedenler kemoterapi ve radyasyon, kemik iliği nakli, oral kontraseptif ilaç kullanımı, hamilelik, polistemi ve protein C eksikliği sayılmaktadır. Nontrombotik nedenler ise karaciğer veya karaciğer dışı kitle lezyonlarıdır (4)(5)(6).…”
Section: Venöz Obstrüksi̇yon (Budd-chiari Sendromu)unclassified
“…According to possible sites of obstruction, BCS may be divided into hepatic vein obstruction, inferior vena cava obstruction and a mixture of hepatic vein and inferior vena cava obstructions. Development of effective vascular surgery and interventional treatment approaches for the treatment of BCS associated with diffuse hepatic vein obstruction is difficult (3,4). Multiple studies have shown that portal vein-vena cava surgical shunt does not increase the survival of BCS patients (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%